The effect of internship programmes on soft skills and work motivation on students' work readiness - Wahyuni, Restu; Suhardi, Suhardi; Amin, Mat (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of internship programs, soft skills, and work motivation on students' work readiness, with self-efficacy as a mediating variable. The study was conducted on Pertiba University students using a quantitative approach using the Partial Least Squares (PLS) method. Data were collected through questionnaires with 178 students as respondents. The results showed that soft skills and work motivation had a positive and significant effect on students' work readiness. Conversely, internship programs did not show a significant effect on work readiness, either directly or indirectly. In addition, self-efficacy was shown to significantly mediate the relationship between soft skills and work readiness, but did not mediate the relationship between internship programs and work motivation on students' work readiness. These findings confirm that students' work readiness is more determined by internal factors, particularly interpersonal skills and self-confidence, than by internship experience alone. Therefore, universities are advised to place more emphasis on the development of students' soft skills and self-efficacy through collaborative learning, self-development activities, and meaningful practical experiences to improve students' readiness to face the increasingly competitive world of work.